Real-time collision avoidance trajectory planner using generalized vector explicit guidance - Subies Hueso, Josep; Mondal, Sabyasachi; Tsourdos, Antonios; Chadwick, Andrew (American Institute of Aeronautics and Astronautics (AIAA), 2023)
In this paper, a new real-time collision avoidance scheme is proposed using Generalized Vector Explicit Guidance (GENEX) law, an optimal guidance algorithm that can simultaneously achieve design specifications on miss distance and final UAV–target relative orientation. Low computation, closed-form expression, and optimal derivation are the key features that make it a potential candidate for real-time applications. The guidance law has been tested through simulations for the two-dimensional scenario, and the results are very satisfactory.